History and the written word documents, literacy, and language in the Age of the Angevins - Bainton, Henry (The Middle Ages Series, 2020)
Drawing on the perspectives of modern and medieval narratology, medieval multilingualism, and cultural memory, History and the Written Word argues that members of an administrative elite demonstrated their mastery of the rules of literate political behavior by producing and consuming history-writing and its documents.